2008
DOI: 10.1007/s10551-008-9795-z
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Motives for Social Initiative: Legitimacy, Sustainability, or the Bottom Line?

Abstract: corporations, social responsibility, corporate citizenship, motives, reputation, legitimacy, image, sustainability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(213 citation statements)
references
References 47 publications
12
183
2
1
Order By: Relevance
“…Whereas earlier findings of Gardberg and Fombrun (2006), Melo and Garrido-Morgado (2012), and Lin et al (2016) showed that CSR improves reputation and that this reputational advantage motivates managers to pursue CSR (Brønn and Vidaver-Cohen, 2009;Babiak and Trendafilova, 2011), our results imply that if an SME starts CSR 9 Does CSR put reputation of SMEs at risk? activities, it creates more exposure to external criticism on its CSR.…”
Section: Implications For Csr Strategies Of Smescontrasting
confidence: 92%
“…Whereas earlier findings of Gardberg and Fombrun (2006), Melo and Garrido-Morgado (2012), and Lin et al (2016) showed that CSR improves reputation and that this reputational advantage motivates managers to pursue CSR (Brønn and Vidaver-Cohen, 2009;Babiak and Trendafilova, 2011), our results imply that if an SME starts CSR 9 Does CSR put reputation of SMEs at risk? activities, it creates more exposure to external criticism on its CSR.…”
Section: Implications For Csr Strategies Of Smescontrasting
confidence: 92%
“…The stakeholders might have different perceptions of the reasons why a company is engaged in CSR activities (Ellen et al, 2006;Bronn & Vidaver-Cohen, 2009;Feldman & VasquezParraga, 2013;Cantrell et al, 2014). The results of this study are consistent with the findings that Health CSR activities have positive and negative motives as perceived by customers, namely Moral, Stakeholder, and Business Motives.…”
Section: Resultssupporting
confidence: 85%
“…Many companies have business cultures that commit to certain business principles and moral duties. This result confirms that instrumental motives revolve fundamentally around managerial beliefs that engaging in social initiatives can have a direct impact on profitability-improving revenue or protecting existing profit levels (Bronn & Vidaver-Cohen, 2009). In this research, Customer Loyalty, as a representation of business performance, can enhance the companies' revenue and profitability.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…This is thus a situation that reinforces the relevance and necessity of legitimacy. Several authors emphasize the importance of the existence of moral and/or ethical leadership, and of good reputation for corporate legitimacy (Bronn and Cohen, 2009;Brønn and Vidaver-Cohen, 2009;Deephouse and Carter, 2005;Dowling and Pfeffer, 1975;Palazzo and Scherer, 2006;Suchman, 1995).…”
Section: Introductionmentioning
confidence: 99%